The new circles of learning : cooperation in the classroom and school - Johnson, David W., 1940- (Association for Supervision and Curriculum Development, 1994)
Reinforces and expands cooperative learning practices found in Circles of Learning: Cooperation in the Classroom, to include the school and district. With thorough descriptions of cooperative learning and its supporting research, the authors explain why cooperation must strengthen schooling at every level.